INTERNAL AND EXTERNAL FACTORS THAT DETERMINED INNOVATION DIFFUSION CHANNELS IN LITHUANIA - Binkauskas, Gintaras (Ekonomika, 2009)
The prevailing opinion in Lithuania is that the country‘s economic growth was determined by the inflow of foreign direct investments (FDI). Their influence on the Lithuanian economy remains unquestionable, however, there is a tendency to overestimate their impact, while other factors are under-estimated or ignored completely when conclusions on their influence on the country‘s economy are drawn. Based on the data of the Department of Statistics of Lithuania, Eurostat, other agencies and the analysis of the research of Lithuanian and foreign academics on FDI, and the impact of the innovations on the country‘s economy, the given study presents the analysis of the three main channels for the technological and innovation diffusion, which have exercised a decisive influence on the economic development in Lithuania over the last decade. They are foreign direct investments, international trade, and the country‘s knowledge capital. These diffusion channels were considerably important in the transition period, however, the creation of original knowledge and innovations, or the creative application of the technology created in other countries and application of the knowledge gained abroad was utilised least. In Lithuania, the creation and adoption of extended modifying innovations and technologies was dominant in terms of innovation modes, while the strategic innovations were created by only 1 percent of Lithuanian enterprises . A comparative analysis of surveys, statistical data, and academic studies was conducted and lead to the conclusion that the main technology and innovation diffusion channel, as well as the main driving force behind Lithuania‘s economy during the transitional period of 1996–2007 was neithert FDI nor the scientific potential of the country, but rather the international trade. In addition, the data suggests that the country‘s scientific potential was ill-prepared for the changes brought on by globalisation and had a very weak impact on the growth of the Lithuanian economy and the economy‘s technological and innovational reorientation, which led to the enterprises searching for other possible sources of innovation. The model for the creation of innovation eacompassing state institutions, the science community and enterprises was not functional during the said period in Lithuania.